Storia di un mercato biologico a Palermo: tra ambientalismo di base e clientelismo (Story of an Organic Farmer’s Market in Palermo: Between Grassroots Environmentalism and Clientelism) - Giovanni Orlando (Coordinamento SIBA, 2012)
This article is available on the website of the old publisher Franco Angeli ( http://www.francoangeli.it/riviste/sommario.asp?IDRivista=152 )